Rainfall and Vegetation Effects on Temporal Variation of Topographic Thresholds for Gully Initiation in Mediterranean Cropland and Olive Groves - Hayas, Antonio; Poesen, Jean; Vanwalleghem, Tom (Land degradation & development, 2017)
Topographical threshold conditions (s ≥ k a−b), expressed by local slope (s) and drainage area (a), have been widely used to predict gully incision locations. However, little attention has gone to the variation of the thresholds over time. Rainfall variability and changing land use or vegetation cover can potentially lead to important shifts in established thresholds. In this study, we determine topographic thresholds for gullies forming under olive groves and herbaceous crops between 1956 and 2013 in a catchment in Southern Spain. For ten different time periods, we then analysed the impact of rainfall, land use and vegetation cover on the variation of these thresholds. The results show similar topographic thresholds for olive groves and herbaceous crops. However, important variations were found over time. Rainfall indexes, in particular rainy day normal, were generally best correlated. Finally, although overall no effect of land use was obtained, the results did show a significant effect of vegetation cover, but mainly in those years where rainfall was low. This seems to indicate that during years with high rainfall, topographic thresholds are primarily controlled by rainfall, while vegetation cover seems to exert a secondary control. Copyright © 2017 John Wiley & Sons, Ltd.